2011
DOI: 10.1155/2011/915326
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Relationship between Parental Involvement and Secondary School Students' Academic Achievement

Abstract: This paper reviews the research literature on the relationship between parental involvement (PI) and academic achievement, with special focus on the secondary school (middle and high school) level. The results first present how individual PI variables correlate with academic achievement and then move to more complex analyses of multiple variables on the general construct described in the literature. Several PI variables with correlations to academic achievement show promise: (a) communication between children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 37 publications
3
73
1
9
Order By: Relevance
“…Across these studies, the Hedge's measure indicated that for overall academic achievement, the effect size for parental expectations was the largest among all the other variables (Hedge's g=.88). The remaining variables (i.e., parent-child communication, parents checking homework, and parental style) all showed medium effect sizes, Hedges' g=.32, .38, and .40 respectively, reinforcing the importance and positive effects of parent involvement in schools (Shute et al, 2011).…”
Section: Parental Involvement and Academic Achievementmentioning
confidence: 83%
See 1 more Smart Citation
“…Across these studies, the Hedge's measure indicated that for overall academic achievement, the effect size for parental expectations was the largest among all the other variables (Hedge's g=.88). The remaining variables (i.e., parent-child communication, parents checking homework, and parental style) all showed medium effect sizes, Hedges' g=.32, .38, and .40 respectively, reinforcing the importance and positive effects of parent involvement in schools (Shute et al, 2011).…”
Section: Parental Involvement and Academic Achievementmentioning
confidence: 83%
“…Secondly, perceived parental involvement was directly and negatively related to academic achievement for all grade levels. Thirdly, that perceived parental involvement predicted academic achievement and fourthly, that higher levels of perceived parental involvement were associated with lower levels of achievement, especially among the tenth graders (Shute, Hansen, Underwood, & Razzouk, 2011). Al-Alwan (2014) extended the parameters of the discourse to include a discussion of the relationship between parental involvement and motivational constructs such as school engagement, as measured by behavioural engagement, www.ccsenet.org/ies International Education Studies Vol.…”
Section: Parental Involvement and Academic Achievementmentioning
confidence: 99%
“…Despite this conceptual difference, in the psychological literature, the constructs of parental aspiration and expectation have often been used interchangeably (Shute, Hansen, Underwood, & Razzouk, 2011;Trusty, 2002;Yamamoto & Holloway, 2010). In fact, some researchers regarded an aspiration item as an index of parental expectation (e.g., Juang & Silbereisen, 2002;Zhang et al, 2011).…”
Section: Potential Negative Effects Of Parental Over-aspirationmentioning
confidence: 99%
“…Many authors find a strong relationship between parental involvement (PI) and school achievement of children, arguing that it can remedy any negative effects from income (Jeynes, 2005;Bouchamma, Lapointe and Richard, 2007;Shute et al, 2011;Porumbu and Necşoi, 2013;Serbin, Stack and Kingdon, 2013). Singh et al (1995) distinguish between four groups of PI: parental aspiration, parent-child communication, home structure (such as discipline and rules), and parental involvement in school activities.…”
Section: Family Contextmentioning
confidence: 99%
“…the support and help that parents provide to their children. Shute et al (2011) classify the activities related to PI into two categories: home activities (aspirations, discussions about school, reading at home, checking homework etc.) and school activities (parents' contacts with the school, participation at parent-teacher meetings, volunteering at school etc.).…”
Section: Family Contextmentioning
confidence: 99%